Tata Kelola Penyimpanan Arsip Dalam Meningkatkan Efesiensi Tata Usaha Lembaga Pendidikan - Fitry, Susanti Arian (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Efficient archive storage is crucial in improving the performance and administration of educational institutions. This article reviews archival storage management strategies that can increase the administrative efficiency of educational institutions. In this paper, researchers use a descriptive qualitative approach with the main source of data being written data related to library management. The collected data was then subjected to data coding, data reduction, and drawing conclusions. Through a literature review and case studies, the importance of implementing organized storage systems, information technology and clear policies is highlighted. Records storage governance plays a very important role in improving the administrative efficiency of educational institutions. By implementing good practices and policies regarding records storage, educational institutions can optimize information and resource management, which in turn improves the quality of the educational services they offer. With a well-organized storage structure, adequate information accessibility, and appropriate use of information technology, educational institutions can reduce time spent on administration, increase data security, and strengthen decision-making processes supported by accurate and reliable information. Apart from that, effective records storage management also contributes to increasing the accountability and transparency of educational institutions. By having a trusted archive storage system, educational institutions can better meet reporting and audit needs, as well as provide easier access for stakeholders to monitor organizational performance and activities. Thus, investment in good records storage management not only brings benefits in increasing the operational efficiency of educational institutions, but also increases the reputation and public trust in these institutions.